Kriteria dan indikator kelestarian hutan yang dikelola oleh masyarakat (community managed forest) - Ritchie, B.; McDougall, C.; Haggith, M.; Burford de Oliveira, N. (Center for International Forestry Research, 2001)
Community managed forest systems embody a considerable portion of the wisdom, knowledge, and practical skills and management necessary for the sustainability of forest resources globally. These systems, however, are under threat in many ways, including from the rapid rate of change of their political, socio-economic, and biophysical contexts. Adapting forest management sufficiently quickly and effectively to meet these changes is both urgent and very challenging. This guide introduces criteria and indicators of sustainability for community managed forest landscapes (CMF C&I) as a potential learning and communication tool that can help meet that challenge. It draws on CIFOR collaborative research on CMF C&I in Brazil, Indonesia, and Cameroon to propose a flexible step-by-step approach to developing and implementing self - or collaborative forest monitoring systems, and gives examples of C&I developed by communities in these countries. The approach is targeted to communities and their partners in forest management, such as NGOs, government, or development projects, who are seeking strategies to improve local well-being and forest sustainability through more effective learning, collaboration, and decision-making in local forest management.